Synthesis, Structure and DNA-Binding Properties of Manganese(II) Complex with 1,3-bis(1-Benzylbenzimidazol-2-yl)-2-oxapropane - Wu, Huilu; Bai, Yuchen; Shi, Furong; Wu, Mingchang; Li, Zhen; Zhang, Yanhui (Asian Journal of Chemistry, 2015)
A five-coordinated manganese(II) complex containing ligand 1,3-bis(1-benzylbenzimidazol-2-yl)-2-oxopropane (bobb), with composition Mn(bobb)(pic)2 (pic = picrate), has been synthesized and characterized. The crystal structure of complex has been determined by single-crystal X-ray diffraction. The manganese(II) complex adopts a distorted square-pyramidal geometry. In addition, DNA-binding properties of the ligand bobb and its manganese(II) complex have been investigated by electronic absorption and viscosity measurements. The experimental results suggest that ligand and manganese(II) complex bind to DNA via an intercalation binding mode and their binding affinity to DNA follows the order of manganese(II) complex greater than ligand bobb.